Arquitetura amplificada: incorporação de dispositivos tecnológicos digitais à arquitetura - Mateus de Sousa Van Stragen (2009)
This dissertation presents a study about the incorporation of digital devices into architecture, focusing on experiences that, through the use of electronically mediated interactions, can enrich the relation between human beings and architectural space. Until a few decades ago, these devices were relatively disconnected from architecture, but recently there has been an increasing amount of experiences where these devices are merged into the fabric that constitutes architecture, influencing thereby the design and the way we experience space. This dissertation has been divided in two parts. The first, which has a theoretical and analytical approach, raises issues about the incorporation of digital devices into architecture. In this discussion, the convergence between architecture and digital devices is analyzed, presenting different kinds of practices and discourses related to interactivity in architecture. Furthermore, this part discusses different kinds of interactions that can take place between people and architectural space, with a focus on systems and tools that make this interaction possible. The second part, analyses a prototypeof an interactive device, developed to allow an empirical investigation of some questions raised throughout the study. In addition, this part raises some technical and methodological issues related to the design and development of interactive devices, through witch it was possible to detect problems that may occur during the development and construction of interactive systems. Through the discussions carried out in this research it was possible to observe theoretical and practical issues related to interactive systems. Here it was evidenced that the interaction and the openness made feasible by digital devices can point to a significant change in architectural practice: the shift from a system that separates the one who designs from the one that uses the space to another system where this separation is weakened. This change can make possible and encourage a continuous modification of the built environment.